Customers Satisfaction on the Retail Banking Sector in Bangladesh: A Case Study in City Bank Limited - Mostofa Jaman Shourov; Abidur Rahman Talukder; Md. Lutfor Rahman (International Journal of Engineering and Management Research, 2018)
Nowadays competition among company to the company very serves, but most of the companies present nearly the same product or service with their competitors. To comprehend from competitors a firm need or offer superior services. Customer satisfaction is now one of the important key factors in the business sector. When it comes to banking sector customer satisfaction level is differentiated to one bank to another, thus measuring customer satisfaction is awfully important. without satisfied customers, the bank cannot exist. This work focus on the customer satisfaction in the retail bank on city bank limited. This research is conducted to affirm customer expectation on retail banking, which is decisive for the growth of the company.